Survival and Growth of Individual Farm Enterprises in Transition Economies: Empirical Evidence from Hungary - Marian Rizov; Erik Mathijs (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 2001)
The new individual firmers face the necessity to decide on how much of their assets should be allocated to the individual firm, i.e. what should be the size and scale of operation. Starting from the Jovanovic's (1982) learning model we develop a theory an implication of which is that individual firms may begin at a small even suboptimal scale of production and then, if merited by subsequent perfirmance, expand. Those firms that are successful will survive and grow, whereas those that are not successful will remain small and may ultimately be forced to exit from the industry. The samples of individual firmers analyzed throughout this paper are drawn from the 1997 firm Household Survey in Hungary. Data on several aspects of household' s human capital, the history of firm enterprise such as age and initial (start-up) size of the individual firm, and the market and industry conditions are available. Our estimation results show that older and larger firms are more likely to survive, firm growth decreases with firm age when firm size is held constant and that the learning considerations are important. An increase of human capital can be expected to improve the effectiveness of a firm operator in allocating the firm's resources and adopting new technologies, which should translate into higher growth and survival rates. On the other hand, a firmer's opportunity for employment outside the sector also increases with his human capital, which raises the probability of switching to part-time firming or exiting the firm sector altogether.
Keywords: D1; D2; Q1; 330; transition economies; individual farming; enterprise survival and growth; Landwirtschaftliches Betriebssystem; Unternehmenswachstum; Privatwirtschaft; Übergangswirtschaft; Ungarn